2021
DOI: 10.3390/cells10071803
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effects of Human Dental Pulp Stem Cells on the Biological Phenotype of Hypertrophic Keloid Fibroblasts

Abstract: Objective: Despite numerous existing treatments for keloids, the responses in the clinic have been disappointing, due to either low efficacy or side effects. Numerous studies dealing with preclinical and clinical trials have been published about effective therapies for fibrotic diseases using mesenchymal stem cells; however, no research has yet been reported to scientifically investigate the effect of human dental pulp stem cells (HDPSCs) on the treatment of keloids. The objective is to provide an experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…In principle, this means that autogenous sources of cell and tissue regeneration are available for NF1 patients (11). This and previous studies show that the constitutive loss of the NF1 gene does not affect the ability of DPSCs to differentiate according to the chosen conditioning of the environment (43)(44)(45). Until now, it was unknown whether DPSCs from teeth in this tumor area have the same differentiation capacity as DPSCs from NF1 patients who have not developed this facial tumor.…”
Section: Discussionmentioning
confidence: 85%
“…In principle, this means that autogenous sources of cell and tissue regeneration are available for NF1 patients (11). This and previous studies show that the constitutive loss of the NF1 gene does not affect the ability of DPSCs to differentiate according to the chosen conditioning of the environment (43)(44)(45). Until now, it was unknown whether DPSCs from teeth in this tumor area have the same differentiation capacity as DPSCs from NF1 patients who have not developed this facial tumor.…”
Section: Discussionmentioning
confidence: 85%
“…Meanwhile, hDPSCs have been shown to have potent immunomodulatory functions in treating systemic lupus erythematosus (SLE) in the SLE MRL/lpr mouse model ( 6 ). Yan et al also indicated that hDPSCs could inhibit the progression of fibrosis in hypertrophic keloids ( 7 ). In addition, they are available from various tissue sources, including dental pulp stem cells, stem cells from exfoliated deciduous teeth, stem cells from apical papilla, periodontal ligament stem cells and dental follicle progenitor cells ( 8 ), and are highly available during tooth extraction, making them a reliable source for periodontal tissue regeneration techniques ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Keloids are benign skin fibroproliferative tumors unique to humans characterized by aggressive fibroblast proliferation, excessive accumulation of extracellular matrix (ECM) (e.g., collagen I and III), long-term continuous fibrosis, and abnormal inflammatory stimuli (Yan et al, 2021;Zhang et al, 2021). Keloids show various cancer-like features, such as aggressive proliferation beyond the original boundary, lack of spontaneous regression, and vascularization ability (Huang and Ogawa, 2020).…”
Section: Introductionmentioning
confidence: 99%